2016
DOI: 10.1016/j.chroma.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between polymerized ionic liquids synthesized using chain-growth and step-growth mechanisms used as stationary phase in gas chromatography

Abstract: In this study the merits of polymerized imidazolium based ionic liquid (PIL) stationary phases obtained via condensation and free radical polymerizations are compared as stationary phases in gas chromatography (GC). Poly(1-vinyl-3-butyl-imidazolium - bis(trifluoromethane)sulfonamide) (poly(ViC4Im(+) NTf2(-))) was obtained via a chain-growth mechanism while poly(propylimidazolium-NTf2) (poly(C3Im(+) NTf2(-))) was synthesized via a step-growth polymerization. The thermal stability of both polymers was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The concern in ionic liquid-covered gas chromatography supports has enlarged afterward their marketable outline in 2008, also today, numerous ionic liquids glazed supports with dissimilar features are viably accessible. Though, one main task for the growth of static stages built on ionic liquids is the research of extremely standardized coverings, which would service decent ultimate regularities as well as extremely active complex partings, also concurrently, deliver extraordinary thermal constancies for the subsequent gas chromatography supports [60][61][62]. At extraordinary temperatures, identical ionic liquid-glazed silica supports can practice flick commotion prominent to a diminution in the analyte retaining periods as well as efficacy.…”
Section: Polymeric Ionic Liquids Centered Static Stages In Gas Chromamentioning
confidence: 99%
See 1 more Smart Citation
“…The concern in ionic liquid-covered gas chromatography supports has enlarged afterward their marketable outline in 2008, also today, numerous ionic liquids glazed supports with dissimilar features are viably accessible. Though, one main task for the growth of static stages built on ionic liquids is the research of extremely standardized coverings, which would service decent ultimate regularities as well as extremely active complex partings, also concurrently, deliver extraordinary thermal constancies for the subsequent gas chromatography supports [60][61][62]. At extraordinary temperatures, identical ionic liquid-glazed silica supports can practice flick commotion prominent to a diminution in the analyte retaining periods as well as efficacy.…”
Section: Polymeric Ionic Liquids Centered Static Stages In Gas Chromamentioning
confidence: 99%
“…At extraordinary temperatures, identical ionic liquid-glazed silica supports can practice flick commotion prominent to a diminution in the analyte retaining periods as well as efficacy. In this respect, polymerized ionic liquids can offer the compulsory replies, preserving the outstanding thermal constancy of the supports, in addition to uniting the chief structures of an ionic liquid as well as the distinctive polymer characteristics for example better automated constancy plus development capability [62][63][64][65].…”
Section: Polymeric Ionic Liquids Centered Static Stages In Gas Chromamentioning
confidence: 99%
“…The polymerization of IL cations/anions to produce PILs is a strategy to increase the thermal stability of IL-based stationary phases and to reduce their tendency of pooling or forming droplets at high temperatures. Roeleveld et al developed two PIL-based stationary phases via both the chain-growth and step-growth methods . The results indicated that PILs generated by the step-growth method produced higher thermal stability (up to 325 °C) compared to the chain-growth PIL (decomposition temperature of 250 °C).…”
Section: Chromatographic and Electrophoretic Separationsmentioning
confidence: 99%
“…7c). The C6A-C10 column was used up to its maximum allowable operating temperature of 240 C, wherein the increase in background signal measured is 15 pA. 41,42 Thus, this temperatures is recommended as the maximum operational temperature for practical use.…”
Section: Column Minimum Allowable Operating Temperature Thermal Stabmentioning
confidence: 99%